Improving Documentation of Inpatient Problem List in Electronic Health Record: A Quality Improvement Project. Issue 8 (19th December 2021) - Rajbhandari, Prabi; Auron, Moises; Worley, Sarah; Marks, Michelle
Abstract : Background: The problem list is critical in electronic documentation. It is a powerful tool for clinical decision-making because it provides a concise view of all patient problems in one place and is also a criterion for the Medicare meaningful use incentive program. Objective: To measure the rate of utilization of problem list in electronic health records (EHR) in a pediatric hospital medicine unit and implement sequential interventions to increase the rate of use of problem list to more than 80% by the end of 2015, as measured by at least one documented hospital problem at discharge. Methods: We performed a quality improvement process starting with a series of educational interventions. Gradual electronic changes were also made in our EHR to reach our goal. Results: The use of the problem list for pediatric hospital medicine rose from 47% to 100% in June 2015 and continues to maintain well above the goal of 80%. The problem list usage throughout the children's hospital also rose to 100% within 9 months of project implementation. Conclusions: Educational interventions and technology leveraging allowed us to achieve and sustain improvement in appropriate problem list usage.